Oligodendrocytes drive neuroinflammation and neurodegeneration in Parkinson’s disease via the prosaposin-GPR37-IL-6 axis - Qiang Ma; Jin-Lan Tian; Yao Lou; Ran Guo; Xiao-Ru Ma; Jian-Bin Wu; Jing Yang; Bing-Jie Tang; Shun Li; Mengsheng Qiu; Shumin Duan; Jing-Wei Zhao; et al. (Cell Reports)
Summary: Parkinson’s disease (PD) is a common neurodegenerative disease and is difficult to treat due to its elusive mechanisms. Recent studies have identified a striking association between oligodendrocytes and PD progression, yet how oligodendrocytes regulate the pathogenesis of PD is still unknown. Here, we show that G-protein-coupled receptor 37 (GPR37) is upregulated in oligodendrocytes of the substantia nigra and that prosaposin (PSAP) secretion is increased in parkinsonian mice. The released PSAP can induce interleukin (IL)-6 upregulation and secretion from oligodendrocytes via a GPR37-dependent pathway, resulting in enhanced neuroinflammation, dopamine neuron degeneration, and behavioral deficits. GPR37 deficiency in oligodendrocytes prevents neurodegeneration in multiple PD models. Finally, the hallmarks of the PSAP-GPR37-IL-6 axis are observed in patients with PD. Thus, our results reveal that dopaminergic neurons interact with oligodendrocytes via secreted PSAP, and our findings identify the PSAP-GPR37-IL-6 axis as a driver of PD pathogenesis and a potential therapeutic target that might alleviate PD progression in patients.